Short-term psychodynamic psychotherapy: a brief history. (December 2019) - Baée, James; Jeyasingam, Neil
Objective: To discuss the development and rationale for different models of short-term psychodynamic psychotherapy. Conclusion: There are a variety of historical reasons for the current climate of short-term dynamic therapies that can help inform upon their application and future directions.